2016
DOI: 10.1186/s12887-016-0721-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing an isiZulu questionnaire with educators in primary schools in Pietermaritzburg to establish a baseline of knowledge of Autism Spectrum Disorder

Abstract: BackgroundAutism Spectrum Disorder (ASD) is a significant childhood disorder and has a growing prevalence rate across the world. It has been identified in children from a wide range of racial groups, ethnicities and socio-economic groups, making it a globally relevant disorder. However, a lack of research on ASD in Africa makes it difficult to determine the prevalence rate, presentation and level of knowledge regarding the disorder locally. Therefore, assessing knowledge of ASD amongst professionals is a usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
3
9
1
Order By: Relevance
“…Overall, in this review we found a lack of knowledge in most of the articles reviewed coinciding with prior reviews [61,62] and other studies [45]. We found that most of the articles revealed low [64,66,68,71,75,76,79,[84][85][86]95] or medium [65,67,73,74,77,78,80,82,91] levels of knowledge about ASD among their participants, coinciding with prior studies [21,25,36,37]. Indeed, most of the studies showed misconceptions [75,85,91] and gaps, or a lack of knowledge [71,77,85,95].…”
Section: Teachers' Knowledge Of Asd and Moderators That Possibly Influence Asdsupporting
confidence: 71%
See 4 more Smart Citations
“…Overall, in this review we found a lack of knowledge in most of the articles reviewed coinciding with prior reviews [61,62] and other studies [45]. We found that most of the articles revealed low [64,66,68,71,75,76,79,[84][85][86]95] or medium [65,67,73,74,77,78,80,82,91] levels of knowledge about ASD among their participants, coinciding with prior studies [21,25,36,37]. Indeed, most of the studies showed misconceptions [75,85,91] and gaps, or a lack of knowledge [71,77,85,95].…”
Section: Teachers' Knowledge Of Asd and Moderators That Possibly Influence Asdsupporting
confidence: 71%
“…In the case of studies with a pre-and post-test, we wrote down the first test result; in the other two situations, we calculated the average among article results. Eleven studies [64,66,68,71,75,76,79,[84][85][86]95] revealed low levels of knowledge regarding ASD among their participants; nine studies [65,67,73,74,77,78,80,82,91] reported medium knowledge, and five studies [65,87,89,90,92] described a high level of knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations